How Common Is Belief in the Learning Styles Neuromyth, and Does It Matter? A Pragmatic Systematic Review - Newton, Philip M.; Salvi, Atharva (Frontiers in Education, 2020)
A commonly cited use of Learning Styles theory is to diagnose learners into one or more of a handful of supposed styles (e.g. Visual, Auditory, Converger) and then design teaching materials that match the diagnosed styles of individual students. A number of reviews, going back to 2004, have concluded that there is currently no empirical evidence that this ‘matching instruction’ improves learning, and it could potentially cause harm. Despite this lack of evidence, survey research and media coverage suggest that belief in this use of Learning Styles theory is high amongst educators. However it is not clear whether this is a global pattern, or whether belief in Learning Styles is declining as a result of the publicity surrounding the lack of evidence to support it. It is also not clear whether this belief translates into action. Here we undertake a systematic review of research into belief in, and use of, Learning Styles amongst educators. We identified 37 studies representing 15405 educators from 18 countries around the world. Self-reported belief in matching instruction to Learning Styles was high, with a weighted percentage of 89.1%, ranging from 58% to 97.6%. There was no evidence that this belief has declined in recent years; 95.4% of trainee (pre-service) teachers agreed that matching instruction to Learning Styles is effective. Self-reported use, or planned use, of matching instruction to Learning Styles was similarly high. From a pragmatic perspective, the concerning implications of these results are moderated by a number of methodological aspects of the reported studies. Most used convenience sampling with small samples and did not report critical measures of study quality. It was unclear whether participants fully understood that they were specifically being asked about the matching of instruction to Learning Styles, rather than alternatives or a broader interpretation of the theory related to preferences or individual differences. There was evidence of effectiveness for educational interventions aimed at helping educators understand the lack of evidence for matching in learning styles, with self-reported belief dropping by an average of 37% following such interventions.